Views and factors influencing Primary Care Practitioner (pcp) interactions with the pharmaceutical industrys representatives in Malaysia: a multi-sectors qualitative study - Salim, Hani; Ping, Yein Lee; Siew, Mooi Ching; Mawardi, Maliza; Wan Idris, Wan Noor Azlin; Harrun, Noor Harzana (UPM Press, 2024)
Introduction: Pharmaceutical companies invested billions in direct marketing to medical practitioners as it increased sales of prescription drugs. Medical professionals believed that their decision-makings was not influenced by such interactions, but studies have shown that engaging with the industry and accepting gifts might lead to impulses to reciprocate, such as prescribing marketed drugs. This study explored the views and experiences of PCP on interactions with the pharmaceutical industrys representatives. Methods: We used qualitative methods using semi-structured interviews among primary care practitioners from three sectors; academic, public and private. Participants were purposively sampled from various sectors. Interviews were audio-recorded, transcribed verbatim, and analysed thematically. Results: A total of 32 participants were interviewed. The ages of the participants ranged from 33 to 53 years. Most of the participants were female, of Malay ethnicity and from the public sector. Four themes emerged from the analysis: (1) Perceived impact of interactions on prescribing habits, (2) Perceived benefit and harm of interactions, (3) Previous positive or negative encounters, (4) the role of geographical, organisational and policy. Conclusion: The study highlighted the views and factors influencing PCP interactions with the representatives of the pharmaceutical industry in Malaysia. Understanding PCPs viewpoints on such interactions could help PCP better navigate their future interactions without compromising their clinical decision-making through multi-agency collaborations and actions.